Nucleosomes and neutrophil extracellular traps in septic and burn patients - Kaufman, Tomás (2017)
NETosis is a host defense mechanism associated with inflammation and tissue damage. Experimental models show that platelets and von Willebrand factor (VWF) are key elements for intravascular NETosis. We determined NETosis in septic and burn patients at 1 and 4days post-admission (dpa). Nucleosomes were elevated in patients. In septics, they correlated with Human Neutrophil Elastase (HNE)-DNA complexes and SOFA score at 1dpa, and were associated with mortality. Patient´s neutrophils had spontaneous NETosis and were unresponsive to stimulation. Although platelet P-selectin and TNF-α were increased in both groups, higher platelet TLR4 expression, VWF levels and IL-6 were found in septics at 1dpa. Neither platelet activation markers nor cytokines correlated with nucleosomes or HNE-DNA. Nucleosomes could be indicators of organ damage and predictors of mortality in septic but not in burn patients. Platelet activation, VWF and cytokines do not appear to be key mediators of NETosis in these patient groups.